Establishment, Differentiation, Electroporation and Nuclear Transfer of Porcine Mesenchymal Stem Cells. Issue 5 (31st August 2015) - Song, Z; Cong, P; Ji, Q; Chen, L; Nie, Y; Zhao, H; He, Z; Chen, Y
Contents: The limited success of somatic cell nuclear transfer (SCNT) is largely attributed to defects in epigenetic reprogramming of the donor genome. Donor cell types with distinct potential competence may offer different epigenetic flexibility for subsequent genome reprogramming in SCNT. Stem cells possibly enable their genomes to be more readily reprogrammed than differentiated cells. To improve the efficiency of cloning, porcine mesenchymal stem cells (pMSCs) were isolated and well identified by 6‐channel flow cytometry and differentiation assays and were used as donors in SCNT. Compared with porcine embryonic fibroblasts (pEFs), our results showed that pMSCs markedly enhanced cloned embryo development in terms of cleavage and blastocyst formation (p < 0.05). To enhance the epigenetic flexibility of pMSCs, classical reprogramming factors (RFs) were transfected by electroporation, and we achieved optimization with ectopic expression of RFs in pMSCs. Our results suggest that the epigenetic status of donor cells has an improvement on genome reprogramming, and multipotent pMSCs favoured subsequent embryonic development.